Zijn de wenschen der socialisten droombeeldig ? : voordracht gehouden te Gent op 8 januari 1883. - Van Beveren, Edmond (Gent : [s.n.], 1883)
Bibliotheek Anseele
Nederlands
Monografie
Keywords: socialisme